Pengaruh Model Ajir dan Pemasangan Mulsa Plastik Terhadap Pertumbuhan Tanaman Cabai Merah (Capsicum Annuum L.) di Perkebunan Afdeling II Labuhanbatu - Gita Juang Mega Syahputra; Yusmaidar Sepriani; Fitrah Syawal Harahap; Ika Ayu Putri Septyani (AGROMAKNA: Jurnal Pertanian dan Peternakan, 2026)
Curly red chili is a woody seasonal plant, growing in areas with tropical climates. This plant can grow and breed in the highlands and lowlands. The aim of this study was to determine the effect of the stake model and the installation of plastic mulch on the growth of red chili (capsicum annuum l.) plants in the Afdeling plantation. II Labuhanbatu. The time of the research was carried out on October 18, 2021 until April 2022. At the Afdeling 2 plantation, kec. West bar kab. Labuhanbatu. The experimental design used in this study used a factorial 3 x 2 Randomized Block Design (RAK). The first factor in this study was the use of the stake model (A) which consisted of three stake models, namely a single perpendicular marker (a1), a single skewed marker (A1), a2) and triangle stake (a3). The second factor in this study was the installation of plastic mulch (M) which consisted of two treatments, namely without mulch (m0) and using silver black plastic mulch (m1). And repeated 3 times so that there are 18 experimental units. The conclusion of the analysis of the results and discussion based on observations and data processed using the SPSS version of the application. 20 it can be concluded that the interaction between the stake model and the installation of plastic mulch did not occur in all observed parameters. The stake model only had a significant effect on the 42 DAP stem diameter parameter, while the installation of plastic mulch had no significant effect on all parameters